2020
DOI: 10.5937/ffr47-28815
|View full text |Cite
|
Sign up to set email alerts
|

Consumer behaviour in online shopping organic food during the Covid-19 pandemic in Serbia

Abstract: The purpose of this paper was to determine whether the Covid-19 Pandemic influenced the change in the extent of online shopping of organic food in Serbia and whether it has led to a change in organic food consumer behaviour. The survey was carried out in Serbia by using a questionnaire developed specifically for this purpose. The total sample size included 1022 respondents of which 90 respondents were online buying organic food during Covid-19 Pandemic. Descriptive statistics and Chi-square test were used to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 21 publications
2
17
0
3
Order By: Relevance
“…The representative sample was chosen by the random selection method. The questionnaire has encompassed questions on the socio-demographic characteristics of consumers (gender, age, level of education, size of household, level of income, place of living), the frequency of the organic products purchase, the consumers' WTP for organic products (nothing more, up to 10%, 10-20%, 20-30% and more than 30%), the assessment of the organic products nutritional value (1)(2)(3)(4)(5) in regard to conventional products, place of purchase of organic product, for whom the organic products are purchased, healthy eating habits, impact of opinions of others on the organic products purchase, the type of organic products purchased and the main reasons and barriers for the consumption of the organic products. The answers received have included 433 respondents that are the consumers of organic products.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The representative sample was chosen by the random selection method. The questionnaire has encompassed questions on the socio-demographic characteristics of consumers (gender, age, level of education, size of household, level of income, place of living), the frequency of the organic products purchase, the consumers' WTP for organic products (nothing more, up to 10%, 10-20%, 20-30% and more than 30%), the assessment of the organic products nutritional value (1)(2)(3)(4)(5) in regard to conventional products, place of purchase of organic product, for whom the organic products are purchased, healthy eating habits, impact of opinions of others on the organic products purchase, the type of organic products purchased and the main reasons and barriers for the consumption of the organic products. The answers received have included 433 respondents that are the consumers of organic products.…”
Section: Methodsmentioning
confidence: 99%
“…Household income also influences the ability and regularity of organic purchases. Yiridoe et al (2005, p.198) emphasize that "empirical evidence supports the hypothesis that product quality characteristics influence consumers' preferences for organic food, with the following being the most important qualities: (1) nutritional value; (2) economic value; (3) freshness; (4) taste and smell; (5) maturity and (6) general appearance (especially of fruits and vegetables)." The findings from the USA by Thompson (1998), as well as by Thompson and Kidwell (1998), showed that the American consumers with the highest level of education were less willing to consume organic products than those with lower education.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It primarily aims to fill the research gap due to a lack of academic studies dealing with the problem. Only a few papers [15][16][17] analyze the sustainability and economic consequences of the food placement crisis, issues related to food quality and safety, and the ongoing conflict between supply and demand. Some indicators important for food placement have been precisely isolated, with the definition of the intensity of their impact, observed overall at the level of the entire FSC, as well as by sectors.…”
Section: Introductionmentioning
confidence: 99%
“…Kao jedan od izvora zdravlja, ali i način smanjenja štetnih dejstava po okruženje, tržište organske hrane sve više beleži tendenciju rasta. Takođe, aktuelna pandemijska situacija, kao i razvoj online trgovine, dodatno doprinosi tome da se organska hrana sve više kupuje posredstvom online kanala (Ćirić, Ilić, Ignjatijević & Brkanlić, 2020). S obzirom na ograničenost ponude i nedostatak vremena, kupovina proizvoda organskog porekla često se obavlja posredstvom web sajtova specijalizovanih prodavnica (Hasanov & Khalid, 2015).…”
unclassified
“…Najčešći motivi za izbor organske hrane jesu, pre svega, briga o zdravlju (Chen, 2009;Hamzaoui Essoussi & Zahaf, 2009;Çabuk et al, 2014;Chen et al, 2014;Basha, Mason, Shamsudin, Hussain & Salem, 2015;Thøgersen, Dutra de Barcellos, Gattermann Perin & Zhou, 2015) i o okruženju (Çabuk et al, 2014;Chen et al, 2014). Na tržištu Republike Srbije (RS) upotreba organske hrane i dalje je u inicijalnoj fazi, uglavnom zbog visokih cena organskih proizvoda (Grubor, Djokic, Djokic & Kovac-Znidersic, 2015;Ćirić et al, 2020), međutim, poslednjih godina tražnja za ovim proizvodima je povećana.…”
unclassified